Designing a Customer Interaction Model with an Emphasis on Electronic Customer Relationship Management in Digital Banking - Azimi, Seyed Mohammad; Aria, Kiumars; Jalali, Seyed Mehdi (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The aim of this research is to design a customer interaction model with an emphasis on electronic customer relationship management in digital banking. Method: This research, in terms of methodology, is qualitative based on grounded theory and in terms of objective, is applied. The participants in the study included experts familiar with the research topic (university professors, bank managers, and marketing managers in public and private banks in Tehran), 12 of whom were selected using purposive sampling. The research tool included semi-structured interviews, the validity of which was confirmed by face validity, and reliability was also calculated with a coefficient of agreement between coders, resulting in a value of 0.83. For data analysis, a three-stage coding method and the level of categorization of factors and components using the Interpretive Structural Modeling (ISM) method were employed. Findings: The results showed that the causal conditions in designing the customer interaction model with an emphasis on electronic customer relationship management in digital banking include infrastructure, brand-related factors, digital banking and information systems, contextual factors including training, customer-related issues and socio-cultural factors, the central phenomenon including brand, digital banking and information systems, intervening factors including motivation and access and application, strategies encompassing management and planning, support and protection, substitution, development of return on investment, and outcomes including relationship management, marketing, performance, and interactions. Conclusion: Financial system and banking planners can use the results of this research to formulate digital banking and improve the quality of banking services.